Optimization of 2‐stage cooperative spectrum for cognitive radio networks using multi‐antenna energy detectors. (2nd January 2020) - Lin, Ping‐Rong; Chen, Cheng‐Yu; Liu, Tao‐Qing; Chen, Jen‐Yeu; Jeng, Shiann‐Shiun
Summary: Cooperative spectrum sensing, a kind of spectrum sensing scheme in cognitive radio (CR), uses multiple CR relays. To increase performance, this study uses multi‐antenna CR relays and beam‐forming reception. The required bandwidth for reporting channels in cooperative spectrum sensing is crucial. Two‐stage cooperative spectrum sensing is proposed to increase performance without increasing the required bandwidth. The cooperative spectrum sensing is also optimized to allow the CR networks to facilitate the best decision‐making. This study determines the detection performance when beam‐forming reception is used. Numerical simulations are used to validate the effectiveness of the method. It is shown that beam‐forming reception outperforms square‐law combining (SLC) for low SNR values. This study proposes a 2‐stage cooperative spectrum sensing method, which uses multi‐antenna CR relays and beam‐forming reception. The cooperative spectrum sensing is also optimized to allow the CR networks to facilitate the best decision‐making. Numerical simulations are used to validate the effectiveness of the method. Abstract : This study proposes a 2‐stage cooperative spectrum sensing method, which uses multi‐antenna CR relays and beam‐forming reception. The cooperative spectrum sensing is also optimized to allow the CR networks to facilitate the best decision‐making. Numerical simulations are used to validate the effectiveness of the method.